Blended Learning Approaches in Language Instruction: A Comparative Study - Dara, Sokha; Vann, Rithy; Pitri, Alisyah; Nilfatri, Nilfatri (Journal International of Lingua and Technology, 2024)
Blended learning, which combines traditional face-to-face instruction with online learning, has gained significant attention in language education due to its potential to enhance flexibility and engagement. Despite its growing popularity, there is limited comparative research on the effectiveness of different blended learning models in language instruction. This study addresses this gap by examining the impact of various blended learning approaches on language learning outcomes. The research aims to compare the effectiveness of different blended learning models in language instruction, focusing on their impact on learner engagement, language proficiency, and satisfaction. It seeks to identify best practices for integrating online and face-to-face components to optimize language learning experiences. A mixed-methods approach was employed, involving 200 language learners divided into three groups, each experiencing a different blended learning model. Data were collected through pre- and post-tests, surveys, and focus group discussions. Quantitative data were analyzed using statistical software, while qualitative data were subjected to thematic analysis. The findings revealed that the flipped classroom model significantly improved learner engagement and language proficiency compared to other models. Participants in the flipped classroom group reported higher satisfaction levels and greater confidence in using the target language. However, all blended learning models showed positive outcomes, suggesting that the integration of online and face-to-face components enhances language learning.